ICT integration into the teaching and learning of science: experiences and perceptions of secondary school teachers - Ogegbo, Ayodele A. (African Perspectives of Research in Teaching and Learning Journal (APORTAL), 2024)
The integration of Information and Communication Technologies (ICTs) in education became crucial after the COVID-19 epidemic. Few studies have examined how ICTs are utilised to teach science in developing nations like Nigeria. This qualitative case study investigated secondary school teachers’ perspectives and experiences with integrating ICTs in science teaching in Nigerian classrooms using semi-structured interviews with six science teachers from an education district in Lagos, Nigeria. Content analysis of the information gathered indicates that sampled teachers demonstrated positive perceptions of performance and effort expectations toward using ICTs in science teaching and learning but rarely used these technologies in their classrooms. The findings attributed sampled science teachers’ low use of technologies to their perceived lack of facilitating conditions, including limited technological resources and access to digital devices, unreliable electricity supply, poor technological pedagogical content knowledge, and lack of support and funding. Thus, teachers should be provided with basic support, access to functioning technical tools like computer laboratories, and effective technology training for scientific teaching and learning
Journal article published in African Perspectives of Research in Teaching and Learning Journal Issue 1, Volume 8, 2024
Keywords: Information and communication technologies; Teachers’ perceptions; Secondary schools; Science education; Unified theory of acceptance; Use of technology; Communication technology; COVID-19 Pandemic, 2020; Education, Secondary; Educational technology; Science -- Study and teaching (Secondary)